Kebutuhan Air Bersih dan Penyaluran Air Buangan Bandara Soekarno Hatta - Ataline Muliasari (Research and Development Agency of The Ministry of Transportation, 2010)
Facilities to support activities at airports such as toilets, mosque until the canteen / resburant would require water as a basic requirement. The more solid the number of apassenger at the arrival and departure terminals, then more and more also needs clean water at the airport. In addition for clean water was provided for passenger, clean water is also needed by the airport staff and other workers who support the activities of these air in airport. By utilizing the formula for calculating water as stated on the air dibandar SKEP 347/XII/99, it is known that the clean water needs in Soekarno Hatta Airport is 641 200 liters daily.